Mortaria in graves - Krekovič, Eduard (Rei Cretariae Romanae Fautorum Acta, 2017)
Mortaria are not found in cemeteries as they did not belong to vessels into which the food for the dead was placed. This view was presented by two Hungarian researchers – L. Barkóczi and E. Bónis – more than half a century ago. Since then the research has progressed and this is the reason why I have decided to follow what kind of changes concerning mortaria in graves have occurred in particular regions of the Roman Empire. I have studied the provinces of Germania, Raetia, Noricum and Pannonia focusing especially on the territories close to the Roman limes where the mortaria occur most frequently. Pannonia is a special case as I have collected mortaria from the graves of the whole province. With the exception of the limes area for other provinces I have chosen also the criteria of the size of the burial site – more than 50 graves and the number of mortaria – more than five. For this reason I have not taken into account smaller cemeteries with more than five mortaria in a grave (e.g. Neuburg an der Donau) or the larger ones with five mortaria or less (e.g. Dillingen).